Prevalence of multimorbidity in people living with and without severe mental illness: a systematic review and meta-analysis - Halstead, S; Cao, C; Mohr, GH; Ebdrup, BH; Pillinger, T; McCutcheon, R; Firth, J; Siskind, D; Warren, N (Elsevier, 2024)
Background: People with severe mental illness (SMI), specifically schizophrenia-spectrum disorder (SSD) and bipolar disorder (BD), face poorer health outcomes from multiple chronic illnesses. Physical multimorbidity, the coexistence of two or more chronic physical conditions, and psychiatric multimorbidity, the coexistence of three or more psychiatric disorders, are both emerging concepts useful in conceptualising disease burden. However, the prevalence of physical and psychiatric multimorbidity in this cohort is unknown. Methods: We searched CINAHL, EMBASE, PubMed, and PsycINFO from inception until 15/02/2024 for observational studies that measured multimorbidity prevalence. From control studies, a random-effects meta-analysis compared odds of physical multimorbidity between people with and without SMI. Absolute prevalence of physical and psychiatric multimorbidity in people with SMI was also calculated. Sensitivity and meta-regression analyses tested an array of demographic, diagnostic, and methodological variables. Results: From 11144 citations we included 82 observational studies featuring 1623773individuals with SMI (specifically SSD or BD), of which 21 studies featured 13235882 control individuals without SMI. The odds ratio (OR) of physical multimorbidity between people with and without SMI was 2.40 (k=11, 95%CI=1.57–3.65, p=0.0009). This ratio was accentuated in younger SMI populations (mean age≤40years, OR=3.99, 95%CI=1.43–11.10), compared to older populations (mean age>40years, OR=1.55, 95%CI=0.96–2.51; subgroup differences p=0.0013). For absolute prevalence, 25% of those with SMI have physical multimorbidity (k=29, 95%CI=0.19–0.32) and 14% have psychiatric multimorbidity (k=21, 95%CI=0.08–0.23). Conclusions: This is the first meta-analysis to estimate physical alongside psychiatric multimorbidity prevalence, demonstrating that these are common in people with SSD and BD. The greater burden of physical multimorbidity in people with SMI compared to those without is potentially magnified for younger cohorts, reflecting a need for earlier intervention. Our findings speak to the utility of multimorbidity for characterising the disease burden associated with SMI, and the importance of facilitating integrated physical and mental healthcare.